PENGARUH RELIGIUSITAS, PENGETAHUAN PRODUK DAN FAKTOR SOSIAL TERHADAP PENGGUNAAN SHOPEEPAYLATER - Fany Fadhila; Azhar; Marpaung, Muslim (Politeknik Negeri Medan, 2020)
This research aim to explain the influence of religiosity, product knowledge and social factor on decision the user of shopeepaylater. The types of data is qualitative data, which is quantitative using a Likert scale. Data collection techniques through questionnaires distributed to 49 respondents. The analysis used in this research is multiple linear regression analysis, make a classic assumption experiment, correlation coefficient, determination test, statistical t-test and statistical F-test. The result showed that product knowledge and social factor partially have a positive, strong and significant effect on decision the user of shopeepaylater, while religiosity partially has a positive, strong and not significant effect on decision the user of shopeepaylater. The variable of religiosity, product knowledge and social factor simultaneously very strong, positive and significant on the decision of shopeepaylater with and effect of 85% and the rest 15% is influenced by the other variables outside of this research. Muslim people who use shopeepaylater are the majority of women with 18-24 years old, latest education is high school, employment status is students with an allowance of 1-3 million and monthly consumption is less than one million.